Oral health and dental treatment needs of people with motor neurone disease. (22nd July 2014) - Tay, CM; Howe, J; Borromeo, GL
Abstract Background People with motor neurone disease (MND) may present with physical limitations impacting on oral health and access to oral health care. This study aimed to assess the oral health status and treatment needs of people with MND in Victoria, Australia. Methods Patients with advanced MND attending a multidisciplinary MND clinic in Melbourne were recruited. Data collection included self‐reporting questionnaires on previous dental experience, current oral hygiene practices and current dietary habits, a medical questionnaire, and a clinical examination charting participants' dentition, restorations, caries and periodontal status, plaque and gingival indices, and assessment of oral health. Results Thirty‐three participants took part in the study with eight self‐reporting regular dental visits. No participant exhibited probing depths of more than 3 mm. Ten out of 27 dentate participants required extractions and restorations for retained roots and caries, while three presented with non‐carious cavities, lost restorations and fractured cusps. Oral health status was not affected by MND presentation in these participants. Conclusions The study found that oral health was not affected by advanced MND. Participants' and clinical teams' motivation towards oral health care may have contributed to oral health. The dental profession should be involved as part of the multidisciplinary effort towards ongoing care.